Diuraphis noxia: reproductive behaviour in Argentina - Ricci, Mónica (2011)
Diuraphis noxia (Kurdjumov) (Rhynchota;Aphididae) is an important aphid pest of wheat and barley crops in many countries. Populations of Russian wheat aphid (RWA) from different origins show different reproductive behaviour, but the situation in Argentina was unknown. The aim of the current research was to determine the reproductive behaviour of RWA in Argentina based on samples from populations at six different localities with contrasting land use, altitude and climate.